Parenteral nutrition in adults during acute illness: a clinical perspective for clinicians. Issue 4 (8th April 2020) - Fetterplace, Kate; Holt, Darcy; Udy, Andrew; Ridley, Emma
Abstract: Parenteral nutrition (PN) is the administration of a nutritional formula by means other than the gastrointestinal (GI) tract. The formula may include carbohydrates, amino acids, lipids, electrolytes and/or micronutrients. The primary indications for PN are intestinal failure (IF) due to an underlying disease or treatment, or if the GI tract is not accessible. The goals of PN should be to ensure adequate nutrition provision to meet patient needs while minimising the risk of complications. PN should be commenced in <48 h in patients who are malnourished or otherwise within 7 days if oral or enteral nutrition is not possible or insufficient. There has been evolution in PN techniques and technology, and the risks associated with PN administration have been reduced. Monitoring clinical, laboratory and metabolic parameters in acute IF is essential to provision of safe nutritional support. When provided to appropriate patients with IF in a timely and considered manner, PN has been shown to be safe, improve nutritional parameters and reduce complications associated with malnutrition. This review aims to provide clinicians a practical guide for the management of PN in adult patients within the acute setting.